School-Assisted Family Communication: A Study on Parent-Child Relationships - Kırat, Emel; Çil, Gürkan; Akgül, Hanife; Acar, Gülümser; Güven, Bülent; Güven, Sibel (Cadernos de Educação Tecnologia e Sociedade, 2024)
This study aims to examine parent-child relationships within the context of school-family collaboration. In the study, which was conducted with the case study design—one of the qualitative research methods—the opinions of seven parents of students receiving education in public primary schools in the 2023-2024 academic year were sought. The opinions obtained through focus group interview method were analyzed using descriptive analysis technique. When the findings were analyzed, the effect of positive communication in terms of parent-child communication styles drew attention. It was concluded that the effective approaches followed in the dimensions of effective listening and empathy contribute to children’s roles in the communication process. While differences in daily communication routines based on needs were noteworthy, cases, where communication was interrupted, stood out with expressions of responsibility. The results achieved for privacy perceptions for school and family showed that this issue was taken into consideration based on parents, but children differed in terms of their different developmental characteristics. While expressions of approval or question were among the words that children frequently repeated, positive, approach-based communication was one of the important elements that will strengthen this process.